PENGEMBANGAN MEDIA E-BOOK DENGAN APLIKASI FLIP CREATOR BERBASIS PENDIDIKAN KONSERVASI PADA PEMBELAJARAN BIOLOGI - Muhammad Asyrofi; Siti Roudlotul Hikamah; Haning Hasbiyati (Pendidikan Biologi,Universitas Islam Jember, 2018)
The development of e-book media by integrating conservation education materials with biology learning which is aims to determine the validity of e book media with the application of flip creator-based conversation education on biology learning. The research procedure used is research and development which begins with research and information gathering in the area BKSDA III of Jember- BBKSDA Jatim, Meru Betiri National Park and MA Ma’arif of Ambulu. Testing product design 1 to get validation value and category 58,5% (valid enough) for conversation educational material expert, 75,4% (valid) for biology subject matter experts and 73,6% (valid) for media expert. Product design 2 to get validation value and category 90,8% (very valid) for conversation educational material expert, 93,9% (very valid) for biology subject matter expert and 92% (very valid) for media expert. Preliminary field testing in average percentages with criteria of 87,4% (very good) for students responses and 79,2% (very good) for teacher response. Operational field testing in average percentages with criteria of 74,8% (good) for students responses and 93,8% (very good) for teachers response. The results in above can be concluded that the product is designed feasible in applying in biology learning with very valid based on validation, both from students responses and very good from teacher responses.